2003
DOI: 10.2308/bria.2003.15.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hurdle Rates on the Level of Escalation of Commitment in Capital Budgeting

Abstract: This study proposes that organizations should consider project hurdle rates, as part of their control system design, to reduce escalation of commitment behavior in managers. In particular, we empirically examined the escalation of commitment tendencies in managers receiving organization-set, self-set, and no hurdle rates. Consistent with prior expectations, we found self-set hurdle rates to be an effective control mechanism resulting in significantly lower levels of escalation of commitment. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 47 publications
1
43
1
11
Order By: Relevance
“…Ghosh (1997) finds that preparing a progress report on the project at the time of the setback can reduce escalation of commitment; however, this study does not address preparing a report during the initial phase of capital budgeting. Studies have also found that the use of organization-set hurdle rates is ineffective in reducing escalation of commitment (Cheng et al 2003;Schmidt and Calantone 2002). As a whole, these studies do not make clear what effect the use of capital budgeting techniques will have on escalation of commitment.…”
Section: Literature Review Escalation Of Commitmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Ghosh (1997) finds that preparing a progress report on the project at the time of the setback can reduce escalation of commitment; however, this study does not address preparing a report during the initial phase of capital budgeting. Studies have also found that the use of organization-set hurdle rates is ineffective in reducing escalation of commitment (Cheng et al 2003;Schmidt and Calantone 2002). As a whole, these studies do not make clear what effect the use of capital budgeting techniques will have on escalation of commitment.…”
Section: Literature Review Escalation Of Commitmentmentioning
confidence: 90%
“…This phenomenon has been studied in many contexts since its introduction to the literature over 30 years ago (Staw 1976), including sports (Staw and Hoang 1995), information technology (Drummond 1996;Keil et al 1994), and management (Miller et al 1997). Accounting researchers have tended to focus on escalation of commitment in a capital investment setting (Schulz and Cheng 2002;Rutledge and Karim 1999;Chow et al 1997;Harrell and Harrison 1994;Kanodia et al 1989), and also on factors that mitigate escalation tendencies (Kadous and Sedor 2004;Cheng et al 2003;Ghosh 1997;Jeffrey 1992;Beeler 1988).…”
Section: Literature Review Escalation Of Commitmentmentioning
confidence: 99%
“…Pemilihan subjek mahasiswa dikarenakan beberapa alasan: 1) Mahasiswa pada tahap tersebut telah banyak belajar tentang BSC dan evaluasi kinerja sehingga dipertimbangkan dapat melakukan penilaian kinerja; 2) Keakraban dengan BSC akan mengurangi bias pengukuran umum dalam hal ini mahasiswa akuntansi yang sudah mendapat mata kuliah akuntansi manajemen (Grevinga 2013); 3) Grevinga (2013) juga menemukan tidak ada bias dalam penggunaan mahasiswa akuntansi manajemen dalam melakukan penilaian kinerja menggunakan BSC karena mahasiswa menggunakan kedua tindakan umum dan unik dalam evaluasi kinerja mereka pada saat pengujian; 4) Clinton (1999) dalam Cheng et al (2003) menyatakan bahwa penelitian-penelitian sebelumnya dalam literatur akuntansi dan manajemen terkait penelitian pertimbangan dan pembuatan keputusan, mahasiswa dibenarkan sebagai pengganti manajer; 5) Ashton dan Kramer (1980) memberikan bukti nyata bahwa dengan penelitian membandingkan antara audit berpengalaman dengan mahasiswa dan hasilnya bahwa mahasiswa audit pengganti yang baik untuk auditor pada tugas penilaian; 6) Nahartyo dan Utami (2015) menyatakan ketika penelitian ditekankan pada aspek kognitif manusia dalam memproses informasi dan mengambil keputusan secara umum, maka penggunaan mahasiswa sebagai penyulih profesional dapat diterima secara ilmiah sehingga penggunaan mahasiswa tidak akan mendistorsi temuan riset; 7) Menggunakan manajer yang sesungguhnya pada perusahaan yang menggunakan BSC dapat mengakibatkan bias, karena penilaianya akan lebih cenderung pada divisi mereka bekerja sehingga hasilnya tidak independent; 8) Literatur psikologi menunjukkan bahwa mahasiswa mampu mengolah informasi yang sama dengan individu profesional dalam eksperimen psikologi (Nahartyo dan Utami 2015).…”
Section: Partisipanunclassified
“…In the context of capital budgeting, Cheng et al. () found that when hurdle rates are set by the project team rather than the decision‐makers, escalation was reduced; mandates imposed from higher levels in the organization are not as effective. Opposite results were found by Boulding et al.…”
Section: Literature Reviewmentioning
confidence: 99%